1986
DOI: 10.1021/ac00124a001
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay-directed chemical analysis in environmental research

Abstract: Reseachof specific chemical compounds that can produce human health or ecological effects is a major research objective in environmental and health sciences. The impact of environmental pollution on human health, including mutagenic and carcinogenic effects, is a primary concern.Cancer is a generic term for various neoplastic diseases that can occur many years after exposure to a carcinogenic substance. The best means of eliminating cancer is to define precisely the nature of the carcinogenic chemical, mixture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
81
0
3

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(85 citation statements)
references
References 20 publications
1
81
0
3
Order By: Relevance
“…This showed that the fractionation unmasked the mutagenic potency of the compounds by separating some of the nonmutagenic cytotoxic compounds from the mutagenic compounds in the mixture. The ability of the fractionation to separate a large amount of nonmutagenic mass from mutagenic mass (Tables 7 and 8, Figure 1) is one of the goals of a successful bioassay-directed fractionation (Schuetzle and Lewtas 1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This showed that the fractionation unmasked the mutagenic potency of the compounds by separating some of the nonmutagenic cytotoxic compounds from the mutagenic compounds in the mixture. The ability of the fractionation to separate a large amount of nonmutagenic mass from mutagenic mass (Tables 7 and 8, Figure 1) is one of the goals of a successful bioassay-directed fractionation (Schuetzle and Lewtas 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Given that these factors vary for the SRM and A-DEP samples, we reasoned that the biologic activities of these DEPs were likely to be different. To assess the potential impact of these differences on mutagenicity, we evaluated the two DEP samples using a bioassay-directed fractionation (Schuetzle and Lewtas 1986) coupled with the Salmonella mutagenicity assay.…”
mentioning
confidence: 99%
“…By examining the biological responses of the different fractions of both diesel PM extracts and biodiesel PM extracts it may be possible to identify the emission source components responsible for biological effects, in much the same way bioassay-directed chemical analysis has been used in other environmental research [30,[33][34][35][36], with possible use of the empirical data in predictive modeling. Incorporating testing of biodiesel emissions may assist in identifying the similarities and differences in the health responses (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Diesel exhaust is believed to consist of thousands of organic constituents and is a major cause of urban pollution (Bayona et al 1988;Draper 1986;Erdinger et al 2005;Mestres 2005;Morville 2006;Ona 2006;Schuetzle 1983;Schuetzle & Lewtas 1986;Seidel et al 2006). A number of studies on the adverse effects of diesel exhaust particles (DEP) on human health, including lung cancer (McClellan 1987;Ichinose et al 1997), allergic rhinitis (Muranaka 1986;Takafuji et al 1987), bronchial asthma-like disease (Sagai et al 1996;Miyabara et al 1998), and disruption of endocrine function, have been reported (Yoshida et al 1999;Watanabe & Oonuki 1999;Tsukue et al 2001Tsukue et al , 2002.…”
Section: Introductionmentioning
confidence: 99%